Reformulasi Konsep Najis Ala Ahmad Hassan (1887-1958) - Aziz, Jamal Abdul (Fakultas Syariah IAIN Purwokerto, 2011)
Ahmad Hassan (1887-1958), prominent figure of Persatuan Islam (Persis) who had critical views on Islamic law, offered a conceptual defiling stilth or najis in the context of ablution in Islamic law. In his view there were three kinds of najis: (i) najis as impurity that must be cleaned before praying (salat); (ii) najis as impurity that was forbidden to eat; and (iii) najis as impurity that contained in heart (qalb). These three kinds of najis, according to Hassan, were absolutely based on the rules in Qur`an and Sunnah of the Prophet. Furthermore we can see many controversial opinions of his views in detail rules in this field. In the first kind of najis, according to him, there were only five or six sorts of impurity that were all human substances, they are feces, urine, blood of menstruation, blood of childbirth, mazi, and wadi. These sorts of impurity purely based on the traditions of the Prophet and other legal reasoning. No other impurity or najis need to be cleanned before praying (salat) excepts those five sorts. So, some sorts of impurity like (spittle of) dog, pig, and animal manure, according to his view were not najis that have to be cleanned before praying. In the second kind of najis, according to Hassan forbidden foodstuffs were only forbidden foodstuffs mentioned in Qur`an. There was no forbidden foodstuff outside the Qur`an. In the third kind of najis, according to him, there was metaphor impurity that was in the hearts of unbelievers. The first and second concept of impurity or najis above are important to be studied furthermore.